2013
DOI: 10.1111/1574-6968.12244
|View full text |Cite
|
Sign up to set email alerts
|

Identification of active oxalotrophic bacteria by Bromodeoxyuridine DNA labeling in a microcosm soil experiments

Abstract: The oxalate-carbonate pathway (OCP) leads to a potential carbon sink in terrestrial environments. This process is linked to the activity of oxalotrophic bacteria. Although isolation and molecular characterizations are used to study oxalotrophic bacteria, these approaches do not give information on the active oxalotrophs present in soil undergoing the OCP. The aim of this study was to assess the diversity of active oxalotrophic bacteria in soil microcosms using the Bromodeoxyuridine (BrdU) DNA labeling techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Calcium oxalate is mainly biomineralized to monohydrocalcite and further to calcite by the action of not yet identified microorganisms (bacteria, fungi). The newly identified oxalotrophic Actinobacteria of the genus Kribbella (Bravo et al, 2013) could be involved in this conversion of the photosynthetically fixed CO 2 from air via oxalate to carbonate in the soil. To my knowledge, the decay of calcium oxalate in the classical objects ( Fig.…”
Section: Calcium As An Essential Growth and Potentially Toxic Elementmentioning
confidence: 99%
“…Calcium oxalate is mainly biomineralized to monohydrocalcite and further to calcite by the action of not yet identified microorganisms (bacteria, fungi). The newly identified oxalotrophic Actinobacteria of the genus Kribbella (Bravo et al, 2013) could be involved in this conversion of the photosynthetically fixed CO 2 from air via oxalate to carbonate in the soil. To my knowledge, the decay of calcium oxalate in the classical objects ( Fig.…”
Section: Calcium As An Essential Growth and Potentially Toxic Elementmentioning
confidence: 99%
“…BrdU is a thymidine analog that gets incorporated into DNA by cells undergoing replication, enabling DNA immunocapturing using BrdU antibodies 20 . This method has been successfully used in soils to probe active microbes 21,22 , however, this technique also suffers technical difficulties, such as a low labeling efficiency which typically require a the large amount of biological material to obtain sufficient amount of labeled DNA for sequencing 15 . Some newer approaches have coupled SIP to single cell analysis using Raman microspectroscopy or NanoSIMS to track metabolically active or newly formed cells 23 by labeling them with H 2 18 O 24 , but these methods currently have relatively low throughput and provide limited phylogenetic resolution.…”
Section: Introductionmentioning
confidence: 99%
“…This is relevant considering that oxalate and its salts are some of the most common organic salt found in soil (Tamer et al 2002), because of its production by many plant families (called collectively oxalogenic plants; Franceschi and Nakata 2005) and fungi (Dutton and Evans 1996). In the context of the OCP, a previous study has suggested the potential role of oxalotrophic bacteria in the alkalinization of the soil near the oxalogenic tree Milicia excelsa (Braissant et al 2004), and more recently, a microcosm experiment allowed the identification of oxalotrophic bacteria metabolically active close to the rhizosphere of the same plant (Bravo et al 2013). However, a study on the diversity of oxalotrophic bacteria in tropical soils, and more importantly in soils influenced by the OCP in which their role is crucial, is still missing.…”
Section: Introductionmentioning
confidence: 99%